Perspektif Generasi Milenial terhadap Efektivitas Pembelajaran Sejarah di Era Pandemi Covid-19 - Rani Valenda; Herdin Muhtarom (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
The Covid-19 pandemic has a major impact among Indonesians, one of which is in the field of education in Indonesia. During the Covid-19 pandemic, all learning activities were carried out online using technological advances in supporting online learning, so that many people did not understand the online learning system that was applied during the Covid-19 pandemic. The purpose of this research is to see the perspective of creating millennials on the effectiveness of learning history in the era of the Covid-19 Pandemic. With quantitative research methods using a questionnaire / questionnaire instrument. The results of this study regarding the perspective of creating millennials on the effectiveness of historical learning in the Covid-19 pandemic era show that creating millennials agrees to apply a historical learning model that uses technological advances with research data of 31 respondents (86.1%).